Pengaruh Kompensasi Dan Motivasi Kerja Terhadap Kinerja Karyawan: Survey Pada Salah Satu Perusahaan Outsourcing di Kota Bandung - Desi Rismawati; Dedi Hadian; Ester Manik; Titi Titi (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
This study examines the effect of compensation and works motivation on employee performance. To determine the magnitude of the effect of compensation and work motivation on employee performance, the researchers surveyed one outsourcing company in Bandung with 45 employees as respondents. The statistical methods used in this research are descriptive and verification methods. This study indicates that all independent variables, namely compensation and work motivation, have a positive relationship and have a significant influence on the dependent variable, namely employee performance. Based on the overall analysis of the data obtained, it knows that the compensation is in a reasonably good category, work motivation is in a reasonably good category, and employee performance is in a reasonably good category. Compensation has a high impact of 30%. In contrast, work motivation has a low effect of 29.5%. It reaffirmed that compensation and work motivation had an effect of 59.4% on employee performance and the remaining 40.6% was influenced by other factors not examined and possibly affecting employee performance.